Accelerating ion diffusion with unique three-dimensionally interconnected nanopores for self-membrane high-performance pseudocapacitors. Issue 46 (16th November 2017) - Gao, Yuan; Lin, Yuanjing; Peng, Zehua; Zhou, Qingfeng; Fan, Zhiyong
Abstract : Three-dimensional interconnected nanoporous structure (3-D INPOS) possesses high aspect ratio, large surface area, as well as good structural stability. Profiting from its unique interconnected architecture, the 3-D INPOS pseudocapacitor achieves a largely enhanced capacitance and rate capability. Abstract : Herein, a unique three-dimensionally interconnected nanoporous structure (3-D INPOS) pseudocapacitor electrode, which possesses a large surface area, an efficient electron and ion transport, together with a remarkable structural stability, has been constructed via soft anodization of an aluminum alloy, cost-effective ultrasonic spray pyrolysis (USP)-assisted deposition of fluorine-doped tin oxide (FTO), and controllable electrochemical deposition of nanostructured manganese dioxide (MnO2 ). Taking the advantage of large surface area, the as-built 3-D INPOS pseudocapacitor electrode exhibits the highest areal capacitance of 540 mF cm −2 and a volumetric capacitance of 135 F cm −3, which is 53% higher than that achieved from the conventional 3-D nanopore pseudocapacitor electrode and 17.6 times higher than that of the planar electrode. More interestingly, the unique 3-D interconnected structure offers an unrestricted space for the diffusion of electrolyte ions. Thus, the 3-D INPOS electrode achieves a higher rate capability than the 3-D nanopore electrode. As a proof of concept, a symmetric self-membrane pseudocapacitor device was constructed by simply stacking two pieces of the 3-D INPOS electrodes. Without an added separator, the device possesses a largely reduced dead volume and achieves the highest volumetric capacitance of 28.9 F cm −3 and a specific energy of 2.36 mW h cm −3 . The largely enhanced capacitance, rate capability, and specific energy certainly make the 3-D INPOS an ideal architecture for the fabrication of high-performance pseudocapacitors.